The role of ablative treatment in differentiated thyroid cancer management. Issue 2 (4th March 2017) - Melo, Miguel; Vicente, Nuno; Ventura, Mara; Gaspar Da Rocha, Adriana; Soares, Paula; Carrilho, Francisco
ABSTRACT: Introduction: The role of ablative treatment in differentiated thyroid cancer management has been evolving over the years. After its introduction in clinical practice, the use of postsurgical radioiodine treatment was generalized to almost every patient with differentiated thyroid cancer, with the exception of unifocal microcarcinomas. However, in the last decade several studies questioned its benefit in low- and intermediate-risk patients. Areas covered: In this review we discuss the role of postsurgical radioiodine treatment at the present time. Expert commentary: Although there is general consensus about the recommendation for very low-risk (microcarcinomas) and high-risk patients – no indication for routine postoperative radioiodine and clear indication for radioiodine treatment, respectively, the recommendation for low- and intermediate-risk patients is still under debate. The most recent guidelines from the American Thyroid Association make a statement against routine postoperative radioiodine in both low- and intermediate-risk cases, recommending an individualized approach that takes into consideration the risk of disease persistence or recurrence after surgery. We consider that these recommendations are in accordance with the best evidence available today, and we would like to emphasize that radioiodine is generally favored for most intermediate-risk patients, especially in the presence of extensive lymph node disease or older age.